Unique Phenotypes With Corresponding Pathology in Late-Onset Hereditary Transthyretin Amyloidosis of A97S vs. V30M - Hsueh, Hsueh-Wen; Chao, Chi-Chao; Chang, Koping; Jeng, Yung-Ming; Katsuno, Masahisa; Koike, Haruki; Hsieh, Sung-Tsang (Frontiers in Aging Neuroscience, 2022)
Objective: Hereditary transthyretin amyloidosis (ATTRv) encompass different phenotypes among various genotypes. Analysis of the natural history and risk factors of faster progression in different genotype would refine the treatment strategy. Methods: The clinical manifestations of ATTRv from A97S (p.A117S) of Taiwanese and late-onset V30M (p.V50M) of Japanese were compared. An autopsy study of A97S was performed. Results: There existed three unique features in the A97S cohort compared to the V30M cohort: (1) dysphagia, (2) carpal tunnel syndrome, and (3) onset age. First, dysphagia was common in A97S (53.4%) but not in V30M and served as a contributor to fast disease progression. All phases of swallowing were affected. In the autopsy pathology, there were extensive amyloid deposits in the viscera and nerves of the tongue, larynx, and esophagus. In A97S, 45 patients (43.3%) had carpal tunnel syndrome history before the onset of length-dependent symptoms by 3 years. The amyloid deposition was more prominent in the median nerve than that in the transverse carpal ligament. The onset age at different stages was younger in the A97S cohort than the V30M cohort by 4~5 years. Conclusion: These phenotypic characteristics together with autopsy pathology in A97S distinct from V30M. Early dysphagia in A97S correlated with fast progression. In A97S, median neuropathy leading to carpal tunnel syndrome might be in a continuous spectrum of ATTRv course rather than an independent disease entity. Such observations may serve as a foundation to explore and analyze unique phenotypes among various genotypes.